The occurrences of «phaneróō» in John 21 and 1 John, example of the Johannine development of the revelation idea - González Carrión, Francisco Javier (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The present contribution, in two installments, explores the extent to which the occurrences of «phaneróō» in John 21, which describe the Resurrection appearances as a «revelation», represent an advance in the theological reflection of the Johannine community, since this verb, in John 1-20, is reserved for Jesus’ ministry as Revealer. A clue to the question lies in analyzing the occurences of «phaneróō» in 1 John, to verify whether the usages this writing assigns to the term remain in the same semantic field as in John 1-20, or whether they are extended to new christological dimensions. The analysis will show that 1 John, on the one hand, retains the usage that John 1-20 assigns to «phaneróō», with some nuances (1 John 1:2; 3:5, 8; 4:9), while, on the other hand, representing a new advance in qualifying the event of the parousia as an act of definitive revelation (1 John 2:28; 3:2). The consideration of the Resurrection as an act of revelation (John 21:1, 14), without espace among the usages that 1 John grants to «phaneróō», would point towards a new enlargement of the semantic field, which would refer to a different stage in the path of theological reflection of the Johannine community. Due to its extension, this installment will be restricted to the analysis of the occurrences of «phaneróō» in 1 John, leaving for a second installment those of the Gospel’s epilogue.
Keywords: to reveal; to show; semantic field; path of theological reflection; Johannine community; Johannine writings